Vine planting rights, farm size and economic performance: Do economies of scale matter in the French viticulture sector? - Bernard Delord; Étienne Montaigne; Alfredo Manuel de Jesus Oliveira Coelho (Wine Economics and Policy, 2015)
This paper assesses the existence of both greater profitability for large-scale farms and economies of scale in the French viticulture sector, thereby confirming or invalidating the argument put forward by the European Commission to justify the abolition of vine planting rights. According to this argument (1) economic efficiency increases with the extension of the vine area in vineyards, and (2) vine planting rights prevent the expansion of farms. This article discusses the issue of economies of scale in agriculture and focuses on specific matters related to viticulture. The key issue of our demonstration lies in the impossibility of defining economies of scale by comparing the profits of farms producing different types of product at different prices. By using an assessment of these variables through FADN, it proposes and justifies the interest of using a measurement of output which is the net value added per unit of labor. The report prepared on behalf of the European Parliament is criticized as it demonstrates a positive correlation between size and efficiency, without taking account of the broad farm gate price dispersion for wine. This article demonstrates that in the case of France, over the period 2005-2007, farm size has little impact on performance. The significant differences observed are the result of differences in the selling price of wine. In summary, the main argument put forward by the European Commission to justify canceling vine planting rights is not adapted to the case of France because it considers wine as a single product sold at a single price.
Keywords: 330; Economies of scale; Planting rights; Price; Profitability; Wine growing farm